A Genetic Variation in the Y Chromosome Among Modern Japanese Males Related to Several Physiological and Psychological Characteristics - Matsunaga, Masahiro; Ohtsubo, Yohsuke; Masuda, Takahiko; Noguchi, Yasuki; Yamasue, Hidenori; Ishii, Keiko (Frontiers in Behavioral Neuroscience, 2021)
Previous studies in population genetics have proposed that the Y-chromosomal (Y-DNA) haplogroup D ancestor likely originated from Africa. The haplogroup D branch next started Out-of-Africa migration, rapidly expanded across Eurasia, and later diversified in East Asia. Y-DNA haplogroup D-M55, one of the branches of haplogroup D, is only found in modern Japanese males, suggesting that individuals with Y-DNA haplogroup D migrated from the Eurasian continent. Based on previous observations, Y-DNA haplogroup D is expected to be associated with some male characteristics including personality. Therefore, this study investigated whether the Y-DNA haplogroup D-M55 is associated with several physiological and psychological characteristics, including exploratory motivation and human relationship-related perception. We recruited Japanese young adult males and females and investigated the association between Y-DNA haplogroup D-M55, physiological (body mass index [BMI]), and several psychological parameters (perceived number of close friends, behavioral inhibition system/behavioral activation system (BIS/BAS), perceived happiness, and perceived loneliness). The results indicated that males with haplogroup D-M55 had a higher BMI and more close friends, compared with non-carrier males. Additional multiple regression analyses, which tested the hypothesis that haplogroup D-M55 predicts BMI and perceived number of close friends confirmed our hypothesis, even after controlling for the potentially confounding variables of age and sex. We also analyzed the gene–gene interaction between haplogroup D-M55 and an autosomal gene polymorphism associated with BMI and human relationships, such as the dopamine D2 receptor gene (DRD2: rs1800497). Results showed gene–gene interactions between haplogroups D-M55 and DRD2 in BMI. Based on these findings, it is demonstrated that Y-DNA haplogroup D is associated with human personality.